Komparasi Konsep Penciptaan Tempat dan Keterikatan Desa Kota : Kasus: Kota Denpasar - Nurwarsih, Ni Wayan; Gede Maha Putra , I Nyoman (RUAS, 2023)
This study aims to compare the concept of place creation and place attachment in Denpasar City, Bali. In the context of rapid urbanization, urban development is becoming increasingly important in maintaining cultural identity and environmental sustainability. The main problem in this study is the difference in understanding and implementation of the concept of place creation and the level of place attachment by communities that focus on rural and urban urbanization. The urgency of the research lies in the need to understand Denpasar City as a center of cultural and tourism activities, blending urban growth with cultural and environmental preservation. The analysis was carried out on a review of government archives in the form of narratives, observations of service use, purchase of goods and vehicle movements, as well as examination of physical and spatial components. The results showed variations in people's perceptions of the concept of place creation, focusing on cultural and environmental preservation. In addition, the degree of attachment to places is related to the active participation of the community in the preservation of the cultural and environmental heritage of the city. This research reveals the importance of integrating people's aspirations in urban planning as well as promoting cultural and environmental sustainability as an integral part of the development of a better Denpasar City.